A Review of Surface Texturing in Internal Combustion Engine Piston Assembly - Mohd Azmi, Muhammad Asyraf; Wan Mahmood, Wan Mohd Faizal; A. Ghani, Jaharah; Mohammad Rasani, Mohammad Rasidi (International Journal of Integrated Engineering, 2020)
This paper presents a brief review of surface texturing with a focus on piston assembly application. The paper begins with a general discussion on surface texturing and the manufacturing process of micro dimples. Further, it discusses the theory of hydrodynamic lift generation and the effect of parameters of micro dimples texture on the surface-to-surface friction. Finally, the effect of surface texturing on heat transfer is briefly discussed. In pursuits to improve internal combustion engine (ICE) efficiency, tribological improvement of moving surfaces by means of micro surface texturing seems to be one of the way. However, texturing parameters have to be carefully designed as it can cause detrimental effect if the designs are wrong. Studies has shown micro surface texturing at piston ring could reduce friction around 20%-50% compare with un-textured piston ring and also reduce fuel consumption at 4%. Micro Surface texturing could also improve heat transfer between the surfaces to reduce piston slap and lubrication oil temperature. As reports on the surface texturing on friction reduction and heat transfer improvement in piston assembly are relatively scarce, it is suggested that optimization of micro dimple parameters for piston skirt application and its effect on engine tribology and heat transfer characteristics be further investigated.